Perancangan Aplikasi Manajemen Tugas Berbasis Android Menggunakan Metode Agile - Listiyanto, Rivaldi; Gunawan, Hendra (Ma'soem University, 2024)
Assignments play a crucial role in the education process. However, the number of assignments can sometimes overwhelm students and make it hard to keep track of them all. As a result, there is a growing need for effective and efficient assignment management applications, especially in today's digital age. This application is specifically designed to help users easily and quickly organize and keep track of their assignments. The goal is to create a user-friendly task management application that will make the learning process more efficient for students. We chose the Agile method for its flexibility and adaptability in responding to changing needs and conditions during the development process. The application includes features like task scheduling, reminders, and special notes for each task, making it easier for users to keep their tasks organized. Through our research, we have successfully designed a prototype Android-based task management application that is ready for implementation.